Find the positive integer x such that
1 0 x 1 = x 2 + x 1 + x 2 + 3 x + 2 1 + x 2 + 5 x + 6 1 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Damn, forgot to divide by x!
excellent...!!
nice, solved in the same way : }
Problem Loading...
Note Loading...
Set Loading...
Note that the RHS of the equation can be rewritten as x ( x + 1 ) 1 + ( x + 1 ) ( x + 2 ) 1 + ( x + 2 ) ( x + 3 ) 1 = ( x 1 − x + 1 1 ) + ( x + 1 1 − x + 2 1 ) + ( x + 2 1 − x + 3 1 ) = x 1 − x + 3 1 = x ( x + 3 ) 3 . Hence 1 0 x 1 = x ( x + 3 ) 3 ⟹ x + 3 = 3 0 ⟹ x = 2 7 . (We can multiply out the x from both denominators since it is clear that x = 0 makes both sides undefined.)